POLITENESS IN COMMUNITY PRACTICE - Indrawati, - (Language Circle: Journal of Language and Literature, 2011)
<!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:1; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:variable; mso-font-signature:0 0 0 0 0 0;} @font-face {font-family:"Arial Narrow"; panose-1:2 11 6 6 2 2 2 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:647 2048 0 0 159 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; mso-fareast-language:EN-US;} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-ansi-language:EN-US; mso-fareast-language:EN-US;} .MsoPapDefault {mso-style-type:export-only; text-align:center;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> People in all types of societies organize themselves in relation to each other for work and other duties, and to structure their interactions. People’s behaviours and roles are guided by prevalent norms and regulations so influential that their particular characteristics might be seen by others as distinctively belong to certain groups of societies. Easterners and Westerners might be seen as having distinctive features regarding politeness in human relation. Eastern societies organize themselves primarily according to behaviours showing polite treatment for the sake of moral sanction and socio-cultural harmony. This probably explains easterners preference for a communal life. As with Western societies, they tend to esteem positive politeness related to intimacy and negative politeness related to individual freedom that is attached to their preference for individualism. Eastern societies and Western societies perform distinctive politeness strategies having their own reasons and tendencies as bounded by pragmatic backgrounds of their existence. Pragmatic aspects include language use of various societies, the direct and indirect utterances, explicature and implicature, politeness strategies and many more. International communication calls for world attention toward respecting these distinctive features of various cultural backgrounds. And the direct realization of this cultural pragmatic communication is looking at and doing communication pragmatically. Key words: politeness strategies, positive politeness, negative politeness, cultural pragmatic communication POLITENESS IN COMMUNITY PRACTICE